Culture and the new geography of social exclusion: The New York experience - Mark Stern; Susan Seifert (Social Work & Society, 2019)
The decline of traditional social welfare mechanisms has increased the threat of social exclusion for marginalized populations in the United States, a threat that is reinforced by the recent wave of anti-immigrant mobilization and enforcement. The threat of increased social exclusion is particularly acute in "global" cities like New York. This paper examines the dilemma facing cultural organizations, artists, and cultural participants. On the one hand, culture can be shown to contribute to increased social connection and improved social wellbeing. At the same time, the cultural sector-like other institutions in contemporary society-has experienced increasing inequality, with richer institutions and high-income neighborhoods enjoying increased cultural opportunities, while institutions serving low-income neighborhoods decline. As with other aspects of welfare services, the question becomes whether the inclusion-promoting aspects of the arts and culture can counter the sector's tendency to reinforce other dimensions of economic and social inequality?